The Fair Housing Act, the Communications Decency Act, and the Right of Roommate Seekers to Discriminate Online - Kevin M. Wilemon (Washington University Journal of Law & Policy, 2009)
This Note will analyze the courts’ recent shift and its potential impact on CDA immunity. Part I examines landmark cases involving the Fair Housing Act and § 3604(c)’s prohibition of discriminatory advertising. It will demonstrate that the broad construction of the Act by the Supreme Court and various courts of appeals is in keeping with the FHA’s policy of promoting fair housing practices to the fullest extent allowable under the Constitution. Part II discusses important cases interpreting the CDA’s § 230 grant of immunity to ISPs hosting third-party content. That Part will show the expansive interpretation courts have given this part of the CDA, including immunizing Web sites from civil rights claims under the FHA. The court decisions that have weakened slightly CDA immunity have not yet led to any successful FHA claims.
Keywords: Internet censorship; Freedom of speech; Housing discrimination; Internet advertising; Internet service providers; Fair Housing Act of 1968; Telecommunications Act of 1996